Achieving Acetylcholine Receptor Clustering in Tissue-Engineered Skeletal Muscle Constructs In vitro through a Materials-Directed Agrin Delivery Approach - Scott, John B.; Ward, Catherine L.; Corona, Benjamin T.; Deschenes, Michael R.; Harrison, Benjamin S.; Saul, Justin M.; Christ, George J. (Frontiers in Pharmacology, 2017)
Volumetric muscle loss (VML) can result from trauma, infection, congenital anomalies, or surgery, and produce permanent functional and cosmetic deficits. There are no effective treatment options for VML injuries, and recent advances toward development of muscle constructs lack the ability to achieve innervation necessary for long-term function. We sought to develop a proof-of-concept biomaterial construct that could achieve acetylcholine receptor (AChR) clustering on muscle-derived cells (MDCs) in vitro. The approach consisted of the presentation of neural (Z+) agrin from the surface of microspheres embedded with a fibrin hydrogel to muscle cells (C2C12 cell line or primary rat MDCs). AChR clustering was spatially restricted to areas of cell (C2C12)–microsphere contact when the microspheres were delivered in suspension or when they were incorporated into a thin (2D) fibrin hydrogel. AChR clusters were observed from 16 – 72 hours after treatment when Z+ agrin was adsorbed to the microspheres, and for greater than 120 hours when agrin was covalently coupled to the microspheres. Little to no AChR clustering was observed when agrin-coated microspheres were delivered from specially-designed 3D fibrin constructs. However, cyclic stretch in combination with agrin-presenting microspheres led to dramatic enhancement of AChR clustering in cells cultured on these 3D fibrin constructs, suggesting a synergistic effect between mechanical strain and agrin stimulation of AChR clustering in vitro. These studies highlight a strategy for maintaining a physiological phenotype characterized by motor endplates (MEPs) of muscle cells used in tissue engineering strategies for muscle regeneration. As such, these observations may provide an important first step toward improving function of tissue-engineered constructs for treatment of VML injuries.